Assessment of Informativity of Dopplerographic Determination of the Ankle-Brachial Index - Aytimova G.Y.1, Rozikhodjaeva G.A.2, Matrizaeva G.Dj.3, Yakubova A.B.4, Rakhmanova N.Kh.5 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The modern concept of the diagnosis of peripheral artery disease is one of the urgent problems of modernmedicine. Peripheral Artery Disease (PAD) is a pathology characterized by the formation of plaques in theperipheral arteries. As reported at the Scientific Session soft the American Heart Association in 2007, theprevalence of asymptomatic PAD in adults in the United States was constantly increasing, and now it isfound in almost 5% of adults aged 40 years and older. In addition, PAD is an indicator of the condition of thearteries and its presence is associated with an increased risk of heart attack and stroke.